O habitus vestibulando para o acesso ao ensino superior em um colégio privado no sul de Minas Gerais - Guimarães, João Vinicius Carvalho (2020)
The middle and elite classes in basic education constitute an important field of study for the Sociology of Education, although little explored. This research, has as theoretical precepts the work the Pierre Bourdieu, especially the notion of habitus, field and capital from his praxiological approach. Precisely it aims to investigate the performance of a specific habitus that expresses itself more strongly in the last year of basic education - the 3rd year of high school - aimed at training for entry into university education in a private school in the south of Minas Gerais. To this specific habitus we call vestibulando habitus. The importance of entrance exams for the Brazilian context was also discussed, the notion of school success and failure based on the importance of the diploma and the recent challenges of high school, based on the work of Pierre Bourdieu, applied based on socioeconomic questionnaires. and semi-structured interviews. Most students are linked to both the traditional middle class associated with the high level of schooling of their parents, and also members of the so-called “new middle class”, based mainly on the possession of economic capital, differently from the research hypothesis that said they were elite groups from the South of Minas Gerais. Thus, the flexibility of the vestibulando habitus becomes visible in the fittings of trajectory based fundamentally on the cultural capital associated with the social origin and on the volume of investments made since childhood.